Corporate social responsibility and bank risk - Florian Neitzert; Matthias Petras (Journal of Business Economics, 2021)
The concept of sustainable banking has developed significantly in recent years. Previous research found that corporate social responsibility reduces firm risk, yet this empirical evidence refers almost exclusively to non-financial companies and it remains unclear whether the risk-mitigating effect stems from the environmental, social, or governance pillar. The paper aims to analyse the impact of corporate social responsibility activities on bank risk and to explore its determinants. Using a sample of 582 banks worldwide over the period from 2002 to 2018, we confirm a risk-reducing effect of the corporate social responsibility activity on an aggregated level. The decomposition of this effect suggests that environmental activities determine this risk mitigation. In contrast, social and governance activities do not show similarly unambiguous results. In this way, our analysis highlights the great importance of environmental aspects in banks' risk management.
Keywords: G21; G32; M14; Q56; 650; Bank risk; Default risk; Portfolio risk; Sustainability risk; CSR; ESG